A implementação da Lei 10.639/2003, a prática docente e a abordagem da História e Cultura Afro-Brasileira nos Livros Didáticos de História do Oitavo Ano - MORAIS, Núbia Alfaia de (2024)
This work investigates the implementation of Law 10.639/03 in school and municipal spaces, which made the teaching of Afro-Brazilian History and Culture mandatory in Brazilian schools, and its influence on the approach to Afro-Brazilian history and culture in History textbooks, focusing on a case analysis of Editora FTD. The study analyzes how this legislation impacted the representation of Afro-Brazilian history and culture in 8th grade textbooks, seeking to identify advances and challenges in the inclusion of this content and ethnic-racial approaches. The results indicate advances in relation to previous editions, but still reveal stereotypes and an emphasis on a racially white and Eurocentric approach. It is concluded that, although the National Textbook Program (PNLD) has the potential to promote a more inclusive education, with regard to Education for Ethnic-Racial Relations], it does not replace the need for engaged teachers and complementary materials to address ethnic-racial relations in History teaching more effectively.